Playing with Race: The Ethics of Racialized Representations in E-Games - Chan, Dean (Internaitonal Review of Information Ethics, 2005)
Questions about the meanings of racialized representations must be included as part of developing an ethical game design practice. This paper examines the various ways in which race and racial contexts are represented in a selected range of commercially available e-games, namely war, sports and action-adventure games. The analysis focuses on the use of racial slurs and the contingencies of historical re-representation in war games; the limited representation of black masculinity in sports games and the romanticization of ‘ghetto play’ in urban street games; and the pathologization and fetishization of race in ‘crime sim’ action-adventure games such as True Crime: Streets of LA. This paper argues for, firstly, a continuous critical engagement with these dominant representations in all their evolving forms; secondly, the necessary inclusion of reflexive precepts in e-games development contexts; and thirdly, the importance of advocating for more diverse and equitable racialized representations in commercial e-games.
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé